Risk factors for postoperative delirium in geriatric patients with hip fracture: A systematic review and meta-analysis - Qi, Yi-ming; Li, Ying-juan; Zou, Ji-hong; Qiu, Xiao-dong; Sun, Jie; Rui, Yun-feng (Frontiers in Aging Neuroscience, 2022)
Abstract Objectives: This systematic review and meta-analysis was conducted to identify the potential risk factors for postoperative delirium in geriatric patients with hip fracture. Methods: PubMed, EMBASE, and Cochrane Library were searched from inception until December 31st, 2021. A combined searching strategy of subject words and random words was adopted. Studies involving risk factors for postoperative delirium in elderly patients undergoing hip fracture surgeries were reviewed. Qualities of included studies were assessed using the Newcastle–Ottawa Scale. Data were pooled and a meta-analysis was performed using Review Manager 5.3. Results: A total of 37 studies were included. The following risk factors were significant: advanced age (per year increase) (OR:1.05, 95%CI 1.04-1.07), age>80 years (OR:2.26, 95%CI 1.47-3.47), male (OR:1.53, 95%CI 1.37-1.70), preoperative cognitive impairment (OR:3.20, 95%CI 2.12-4.83), preoperative dementia (OR:2.74, 95%CI 2.18-3.45), preoperative delirium (OR:9.23, 95%CI 8.26-10.32), diabetes (OR:1.18, 95%CI 1.05-1.33), preoperative functional dependence(OR:1.31, 95%CI 1.11-1.56), ASA level (per level increase) (OR:1.63, 95%CI 1.04-2.57), ASA level≥3(OR:1.76, 95%CI 1.39-2.24), low albumin(OR:3.30, 95%CI 1.44-7.55), medical comorbidities (OR:1.15, 95%CI 1.06-1.25), Parkinson’s disease(OR:4.17, 95%CI 1.68-10.31) and surgery delay>48 hours(OR:1.90, 95%CI 1.36-2.65). Conclusions: Clinicians should be alert to patients with those risk factors. To identify the risk factors more precisely, more research studies with larger sample size and better design should be conducted.